Pediatric NAFLD: an overview and recent developments in diagnostics and treatment. (4th May 2019) - Draijer, Laura; Benninga, Marc; Koot, Bart
ABSTRACT: Introduction : Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and adults in industrialized countries. Besides liver-related morbidity, NAFLD is also associated with an increased risk of cardiovascular disease, type 2 diabetes and mortality at adult age. However, despite the high prevalence and serious complications, diagnosing and staging of disease remains complicated due to a lack of accurate screening tools and non-invasive methods to detect fibrosis. Areas covered : Recent insights in epidemiology, pathogenesis, diagnostic evaluation and treatment options in pediatric NAFLD are being reviewed, with a particular focus on new developments in diagnostic tools. Expert opinion : Due to their long life span, children with NAFLD are particularly at risk of complications in their lifetime. Therefore, an effective screening strategy for children to identify those with NAFLD at risk of complications is urgently needed. This is further underscored by new pharmacological therapies that are expected to become available in the next 5 years. Momentarily no accurate non-invasive method for diagnosing pediatric NAFLD is available. New promising biomarkers and imaging tools could hopefully provide better screening tools and could contribute to the development of a successful management plan to identify children with NAFLD.